Evolution of streamflow patterns in Goulburn-Broken catchment during 1884–2018 and its implications for floodplain management. (June 2020) - Patil, Rupesh; Wei, Yongping; Pullar, David; Shulmeister, Jamie
Highlights: Streamflow patterns: critical connections between rivers, floodplains and wetlands. River regulation and diversion evolved patterns of streamflow in Goulburn-Broken catchment. Loss of critical time-varying streamflow elements affected floodplain ecology and biota. Riverine functional flow is proposed to restore flow variability to manage floodplain ecosystems. Abstract: Development of water resources infrastructure largely decoupled floodplains and wetlands from rivers due to alteration of streamflow patterns. However, there is limited understanding of undesirable changes in streamflow patterns due to flow regulation. This study aimed to examine effects of flow regulation and rainfall variation on: 1) long-term flow, 2) upstream and downstream flow, and 3) seasonal flow patterns in the Goulburn-Broken catchment in Victoria, Australia, and discuss the implications for floodplains and wetlands. The non-parametric Mann-Kendall test and other statistical methods were used to analyse changes in long-term (1884–2018), upstream and downstream (1977–2018), and seasonal flow patterns of Goulburn River. Results showed that average annual discharge of Goulburn River decreased over 59% during the post-change period (1957–2018) as compared to pre-change (1884–1956) discharge mainly due to flow regulation and diversion (>86%). This reduced frequency of overbank flows from once every 1.6 years in the pre-change period to once every 5 years in the post-change period. This extended disconnection of floodplains from the Goulburn River has had detrimental effects on biota. Finally, generation of adequate overbank flows and maintaining natural variability of high and low flows with a riverine functional flow approach is recommended to rejuvenate floodplains and wetlands.